Distribution of Diabetic Neovascularization on Ultra-Widefield Fluorescein Angiography and on Simulated Widefield OCT Angiography - Russell, Jonathan F.; Flynn, Harry W.; Sridhar, Jayanth; Townsend, Justin H.; Shi, Yingying; Fan, Kenneth C.; Scott, Nathan L.; Hinkle, John W.; Lyu, Cancan; Gregori, Giovanni; Russell, Stephen R.; Rosenfeld, Philip J. (American journal of ophthalmology, 2019)
Areas of neovascularization (NV) in proliferative diabetic retinopathy (PDR) on ultra-widefield (UWF) fluorescein angiography (FA) were identified and compared with a simulated widefield (WF) swept-source OCT angiography (SS-OCTA) field of view to determine whether the WF SS-OCTA field of view was sufficient for detection of NV in PDR. Retrospective, consecutive case series. All patients with PDR and UWF FA imaging at the Bascom Palmer Eye Institute over a period of 5.5 years were identified. UWF FA images were reviewed and sites of NV were identified either as NV of the disc or NV elsewhere. Sites of NV elsewhere were classified by disc-centered retinal quadrants. A simulated WF SS-OCTA montage field of view was overlaid on the UWF FA images to determine whether sites of NV would have been identified by this simulated WF SS-OCTA field of view. A total of 651 eyes with PDR from 433 patients had at least 1 UWF FA with NV. Of the 651 eyes, 50% were treatment-naïve, 9.8% had NV of the disc only, 41.8% had NV elsewhere only, and 48.4% had both NV of the disc and NV elsewhere. NV elsewhere was most prevalent in the superotemporal quadrant and the least prevalent in the nasal quadrants. When the simulated WF SS-OCTA field of view was overlaid on the UWF FA, 98.3% of all eyes, 99.4% of treatment-naive eyes, and 97.2% of previously treated eyes had NV within the WF SS-OCTA field of view. In those eyes with a repeat UWF FA within 6 to 18 months of the first FA, the distribution of NV did not change in either the treatment-naive or previously treated eyes. NV elsewhere in PDR was most prevalent superotemporally, and 99.4% of treatment-naïve eyes had NV within the simulated WF SS-OCTA field of view. Combined with previous research using WF SS-OCTA to identify NV in PDR, these findings suggest that WF SS-OCTA may be the only imaging modality needed for the diagnosis and longitudinal management of PDR.